HUBUNGAN INDEKS MASSA TUBUH DAN JENIS KELAMIN DENGAN DERAJAT KEPARAHAN CARPAL TUNNEL SYNDROME DI RSUD KOTA MATARAM - Pande Kadek Deva Widya Iswara Oka; Sukandriani Utami; Nyoman Cahyadi Tri Setiawan; I Wayan Tunjung (Yayasan Nusantara Hasana Berdikari, 2023)
Carpal Tunnel Syndrome (CTS) is a common disorder with symptoms involving the median nerve. The risk factors for the occurrence of CTS are grouped into individual and physical factors related to work. Individual factors consisted of a history of diabetes mellitus, hypothyroidism, obesity, rheumatoid arthritis, age and gender. In addition, there are work-related physical factors, namely work with repetitive hand movements, gripping or clamping work with force, abnormal postures on the wrist for a long time. Purpose to determine the relationship between BMI and gender with the degree of severity of CTS in Mataram City Hospital. Observational analytic quantitative research with a cross-sectional study design. The sampling technique used a random sampling technique of 34 samples. The research was conducted at the Mataram City Hospital, from November to December 2022. The data obtained was analyzed using the spermaman rank test. Results of the 34 study samples, there were 8 people (23.5%) with BMI < 24.9 kg/m2 and, 26 people (76.5%) with BMI ≥ 25 kg/m2. A total of 13 men (38.2%) and 21 women (61.8%) suffered from CTS. The value of p = 0.001 (p <0.05) with a correlation value of 0.528 for the relationship between BMI and the severity of CTS, and p = 0.001 (p <0.05) with a correlation value of 0.531 for the relationship between gender and the severity of CTS . There is a significant relationship between BMI and gender with the degree of severity of CTS in Mataram City Hospital.